Streptococcus pneumoniae upregulates Toll2, Toll9, and defensin genes in Bombyx larvae infection model - Farhan R. Chowdhury; M. Ismail Hossain; Tangerul A. Jepu; Nusrat U. A. Saleh; Fatema T. Zohora; Tasmim A. Saleh; Mrinmoy Sarker; Al Numan; Zainab Yousuf; M. Aftab Uddin; Muktadir S. Hossain (PLoS ONE, 2026)
Pneumococcal diseases caused by the human pathogenic bacterium Streptococcus pneumoniae are a major public health concern worldwide. In this study, we examined the pathogenicity of a clinical isolate of S. pneumoniae in the silk moth, Bombyx mori , larvae infection model. The whole genome sequencing of a clinical isolate of S. pneumoniae , Spn1 identified the presence of genes responsible for its virulence and antibiotic resistance. Spn1 infection of Bombyx larvae resulted in death within 24 h concomitant with an increase of phenoloxidase activity in the hemolymph. The bacterial load increased in the hemolymph within 9 h post-infection (p.i.) Ampicillin, ceftriaxone, tetracycline, imipenem, and erythromycin showed therapeutic effect in infected larvae, although the bacterial strain was resistant to erythromycin in vitro . The Bombyx homologs of mammalian TLR2 and TLR4 , known as BmToll2 and BmToll9 ( BmToll9−1 and BmToll9−2 isoforms), were upregulated in both the fat body and trachea. The antimicrobial peptide (AMP) genes, BmdefensinA and BmdefensinB , known to be regulated by the Toll signaling pathway, were significantly upregulated in both fat body and trachea after S. pneumoniae infection through hemolymph. Our data indicate that the Bombyx larvae can be a suitable infection model to study the pathogenicity of S. pneumoniae .